ChemInform Abstract: Total Synthesis of Syringolin A and Improvement of Its Biological Activity. Issue 40 (30th September 2014) - Chiba, Takuya; Hosono, Hidetaka; Nakagawa, Koji; Asaka, Masahiro; Takeda, Hiroshi; Matsuda, Akira; Ichikawa, Satoshi
Abstract An intramolecular Ugi three‐component reaction in the last stage of the syntheses is used for the preparation of Syringolin A (Ia) as well as a set of structure‐based analogues.